2013
DOI: 10.1371/journal.pone.0069782
|View full text |Cite
|
Sign up to set email alerts
|

The C57BL/6J Mouse Exhibits Sporadic Congenital Portosystemic Shunts

Abstract: C57BL/6 mice are the most widely used strain of laboratory mice. Using in vivo proton Magnetic Resonance Spectroscopy (1H MRS), we have repeatedly observed an abnormal neurochemical profile in the brains of both wild-type and genetically modified mice derived from the C57BL/6J strain, consisting of a several fold increase in cerebral glutamine and two fold decrease in myo-inositol. This strikingly abnormal neurochemical “phenotype” resembles that observed in chronic liver disease or portosystemic shunting and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
84
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 57 publications
(91 citation statements)
references
References 44 publications
6
84
1
Order By: Relevance
“…When neurochemical profiles of the mice were compiled, 1 WT mouse and 3 Sca1 154Q/2Q mice (all from different litters) were found to have an abnormal ‘high Gln’ profile that was previously described in the brains of both WT and genetically modified mice derived from the C57BL/6 strain (Tkáč et al 2011; Cudalbu et al 2013). The abnormal profile consisted of 2–3 fold higher Gln, 15–45% lower myo -Ins and 10–20% lower Tau relative to other WT or Sca1 154Q/2Q mice, respectively, at the same age.…”
Section: Resultsmentioning
confidence: 67%
See 3 more Smart Citations
“…When neurochemical profiles of the mice were compiled, 1 WT mouse and 3 Sca1 154Q/2Q mice (all from different litters) were found to have an abnormal ‘high Gln’ profile that was previously described in the brains of both WT and genetically modified mice derived from the C57BL/6 strain (Tkáč et al 2011; Cudalbu et al 2013). The abnormal profile consisted of 2–3 fold higher Gln, 15–45% lower myo -Ins and 10–20% lower Tau relative to other WT or Sca1 154Q/2Q mice, respectively, at the same age.…”
Section: Resultsmentioning
confidence: 67%
“…The abnormal neurochemical profile was observed at all scans throughout the life span of these mice. This profile was recently shown to occur in as many as 25% of the animals from the C57BL/6 background and to be associated with portosystemic shunting in the liver (Cudalbu et al 2013). Since portosystemic shunting causes alterations in gene expression in many organs and an abnormal neurochemical profile in the brain, these four mice were excluded from further analysis.…”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“…However, further research is warranted to elucidate how Nrf2 can affect Creb levels. Another study using Nrf2 knockout mice showed that 2/3 of these mice have a congenital intrahepatic shunt (a much higher percentage than what is expected in the C57Bl6 mice [42]) that affects the hepatic oxygen and protein expression gradients [43]. In these mice, Pepck showed a more diffused expression not only confined to the periportal zone but expanding to both periportal and centrilobular areas due to the difference in oxygen tension.…”
Section: Discussionmentioning
confidence: 99%